Pengaruh Live Streaming, Product Quality Dan Trust Terhadap Impulsive Buying Dirumah Kosmetik Belleza Kecamatan Mojoagung Kabupaten Jombang - ‘ Aini, Nur; Arifin, Rois; Arsyianto, Muhammad Tody (UNIVERSITAS ISLAM MALANG, 2025)
Abstract This research seeks to examine and clarify the impact of three independent variables: Live Streaming, Product Quality, and Trust on the dependent variable, Impulsive Buying at Beleza Cosmetics House, located in Mojoagung District, Jombang Regency. Data gathering utilized the Purposive Sampling Method through the distribution of Likert-scale questionnaires, yielding a total of 75 responses collected. The collected information was then analyzed using the Multiple Linear Regression Method along with Hypothesis Testing, which included the F Test (Simultaneous Test) and the T Test (Partial Test), aided by IBM SPSS Version 25 Software. The study's outcomes collectively indicate that the three independent variables Live Streaming, Product Quality, and Trust significantly affect Impulsive Buying at Beleza Cosmetics House in Mojoagung District, Jombang Regency. Partial/Single Test Outcomes Indicate That Live Streaming Influences Impulse Buying Significantly, Product Quality Affects Impulse Buying Significantly, While Trust Does Not Significantly Impact Impulse Buying. Keywords: Live Streaming, Product Quality, Trust, Impulse Buying